THE INDUSTRIAL REVOLUTION AND ITS CONSEQUENCES AS REVEALED IN DICKENSÃ¢â¬â¢ GREAT EXPECTATIONS - Hetami, Fatma (Language Circle: Journal of Language and Literature, 2009)
A work of literature cannot be separated from its time and place, in which it is made. Therefore, to get a vivid understanding of a literary work, some certain techniques are needed. One of them is by breaking down the social and cultural layers of the work. It can also be applied in DickensÃ¢â¬â¢ novel Great Expectations. By breaking down and analyzing its social and cultural layers, it can be found that the novel reflects the portrait of Industrial Revolution era and its consequences such as dissolution of family units, illness, poverty, mutual exploitation, human passions, expectations, and selfishness as well. ÃÂ  Keyword: Industrial Revolution, society, culture, zeitgeist, social and cultural layers